CAUSES OF THE ORIGIN OF THE CURRENTLY COMMON ISCHEMIC HEART DISEASE (Academia Science Repository, 2023)
It's heart problems caused by narrowed heart arteries. When arteries are narrowed, less blood and oxygen reach the heart muscle. This is also called coronary artery disease and coronary heart disease. This can lead to heart attack. Ischemia often causes chest pain or discomfort known as angina pectoris.